Activities of Non-State Actors and Redefining the Concept of International Legal Personality - Pouria Askari; Zahra MoshrefJavadi (پژوهشهای حقوقی)
A controversial issue in international law is how international legal personality is defined or by what criteria it is conferred. The field mainly tries to address the questions that who has international legal personality, and what characteristics the actor must be endowed with, to be the subject of international law thereafter. scholars and theorists in international law have sought to define the standards and criteria in order to recognize the international legal personality. International law takes different approaches to the issue of international legal personality and specifies the status of actors, as Subject or Object, based on different factors and circumstances. In the beginning, the presence of states was the focus, however, other actors in the international system took on different forms gradually. Besides, International organizations and non-governmental entities such as non-governmental organizations (NGOs), companies, armed groups, etc. appeared on the international scene. therefore, we gradually observe that the influential factors and the definition of the international legal personality have transformed. Thus, nowadays, international law requires specifying the type of its relationship with these actors in order to preserve its function. This article represents the challenges of international law encountering non-state actors through the lens of international legal personality to determine how non-state actors are addressed by international law.